Teething trouble - Chai, W.L. (2001)
Sir,— I read with interest the article by M. P. Ashley 'It's only teething. A report of the myths and modern approaches to teething.' (British Dental Journal2001; 191: 4–8). As a dentist with a nine month-old daughter, this topic is definitely of my concern.